Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2019)
A dataset containing 1356775 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Tupistra Ker Gawl.", "TaxonKey is Speirantha Baker", "TaxonKey is Semele Kunth", "TaxonKey is Ruscus L.", "TaxonKey is Polygonatum Mill.", "TaxonKey is Peliosanthes Andrews", "TaxonKey is Ophiopogon Ker Gawl.", "TaxonKey is Nolina Michx.", "TaxonKey is Maianthemum F.H.Wigg.", "TaxonKey is Eriospermum Jacq. ex Willd.", "TaxonKey is Dracaena Vand. ex L.", "TaxonKey is Danae Medik.", "TaxonKey is Convallaria L.", "TaxonKey is Comospermum Rauschert", "TaxonKey is Calibanus Rose", "TaxonKey is Aspidistra Ker Gawl.", "TaxonKey is Xerolirion A.S.George", "TaxonKey is Thysanotus R.Br.", "TaxonKey is Lomandra Labill.", "TaxonKey is Laxmannia R.Br.", "TaxonKey is Eustrephus", "TaxonKey is Cordyline Comm. ex R.Br.", "TaxonKey is Chamaescilla F.Muell. ex Benth.", "TaxonKey is Arthropodium R.Br.", "TaxonKey is Triteleiopsis Hoover", "TaxonKey is Triteleia Douglas ex Lindl.", "TaxonKey is Petronymphe H.E.Moore", "TaxonKey is Muilla S.Watson, 1879", "TaxonKey is Milla Cav.", "TaxonKey is Jaimehintonia B.L.Turner", "TaxonKey is Dichelostemma Kunth", "TaxonKey is Dandya H.E.Moore", "TaxonKey is Brodiaea Sm.", "TaxonKey is Bloomeria Kellogg", "TaxonKey is Bessera", "TaxonKey is Androstephium Torr.", "TaxonKey is Hemiphylacus S.Watson", "TaxonKey is Asparagus Tourn. ex L.", "TaxonKey is Aphyllanthes L.", "TaxonKey is Yucca L.", "TaxonKey is Schoenolirion Torr.", "TaxonKey is Paradisea Mazzuc.", "TaxonKey is Leucocrinum Nutt. ex A.Gray", "TaxonKey is Hosta Tratt.", "TaxonKey is Hesperocallis A.Gray", "TaxonKey is Herreriopsis H.Perrier", "TaxonKey is Herreria Ruiz & Pav.", "TaxonKey is Hastingsia S.Watson", "TaxonKey is Echeandia Ortega", "TaxonKey is Chlorophytum Ker Gawl.", "TaxonKey is Camassia Lindl.", "TaxonKey is Beschorneria Kunth", "TaxonKey is Behnia F.Didrichs.", "TaxonKey is Anthericum L." ] } The dataset includes 1356775 records from 1336 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004791-190320150433242/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences